Determinants of Savings and Remittances – Empirical Evidence from Immigrants to Germany - Mathias Sinning (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
This paper investigates the determinants of migrants' financial transfers to their home country using German data.A double-hurdle model is applied to analyze the determinants of the propensity to send transfers abroad and the amount of transfers.The findings reveal that return intentions positively affect financial transfers of immigrants to their home country. Moreover, while the effect of the household size on migrants' transfers abroad turns out to be significantly negative, remittances are higher if close relatives live in the sending country. Finally,Vuong-tests indicate that the double-hurdle model is the correct specification for the analysis of migrants' savings and remittances rather than the conventional Tobit model usually applied in the literature. - International migration, savings, remittances This paper analyzes whether immigrant families facing credit constraints adopt a family investment strategy wherein,upon arrival,an immigrant spouse invests in host country-specific human capital while the other partner works to finance the family's current consumption. Using data for West Germany, we do not find evidence for such a specialization strategy.We further examine the labor supply and wage assimilation of families whose members immigrated together relative to families whose members immigrated sequentially. Our estimates indicate that this differentiation is relevant for the analysis of the labor market activities of migrant households.
Keywords: F22; C34; D12; D91; 330; Rücküberweisung (Migranten); Sparen; Migranten; Mikroökonometrie; Schätzung; Deutschland